Evaluating the feasibility and acceptability of a co-design approach to developing an integrated model of care for people with multi-morbid COPD in rural Nepal: a qualitative study. Issue 1 (20th January 2021) - Yadav, Uday Narayan; Lloyd, Jane; Baral, Kedar Prasad; Bhatta, Narendra; Mehata, Suresh; Harris, Mark
Abstract : Objective: To understand the feasibility and acceptability of a co-design approach to developing an integrated model of healthcare for people with multi-morbid chronic obstructive pulmonary disease (COPD) in rural Nepal. Settings: A rural setting of Nepal. Participants: Data collection included five video recordings, five key informant interviews and observation notes from a final co-design workshop that involved a total of 68 stakeholders: persons with COPD and their family members; healthcare providers, including respiratory physicians; local community leaders; representatives from local, provincial and federal government; academics; and representatives from non-government organisations. Primary and secondary outcome measure(s): Feasibility and acceptability of using a co-design approach to develop an integrated model of care for people with multi-morbid COPD in rural Nepal. Results: Our qualitative evaluation of the Hasso Plattner's co-design process found that all stakeholders (including people with COPD/community members, primary care practitioners and local government/senior health officials) were actively engaged in and significantly contributed to the process of co-design. Four main themes were identified which determined the feasibility and acceptability of the resulting integrated model of care: engagement of stakeholders, factors contributing to the co-design, consequences of the co-design process, and challenges and opportunities learnt by the researchers and participants in the co-design process. Based on the relationship between the four main themes emerging from this research, we developed an evaluation framework to guide the co-design of a health service innovation. Conclusion: Our study demonstrated the feasibility and acceptability of the Hasso Plattner's co-design process. Our findings suggest that this co-design approach can be useful and acceptable to local communities and government agencies. It enabled the meaningful contribution of a diverse group of stakeholders in the design and delivery of health services in low-income and middle-income countries.